Telerehabilitation as a physical therapy solution for post-stroke patient in COVID-19 pandemic situations: a review - I Made Yoga Prabawa; Dedi Silakarma; M. Widnyana (Intisari Sains Medis, 2021)
Background: Stroke is one of the leading causes of disability among the adult population. One-third of post-stroke patients require ongoing physical rehabilitation to improve their motoric function. But in this COVID-19 pandemic situation, all outpatient visits or non-emergency cases, including in-clinic physical rehabilitation therapy, have been postponed and limited to maintain physical distancing to prevent the spreading of infection. Telerehabilitation can be the answer to overcome this circumstance.Methods: We conducted a comprehensive search for online literature or studies in 2020. We explored evidence using the following database Cochrane Library, PubMed, and Google Scholar. The keywords used to obtain the relevant research include “telerehabilitation” OR “telemedicine” AND “physical rehabilitation” AND “stroke patient” AND “COVID-19 pandemic”. The literature was analyzed based on the results of previous studies.Results: Telerehabilitation delivers rehabilitation services via communication technologies involving the patient and the physical therapist communicate using telehealth platform and video-teleconference. Several telerehabilitation techniques can be used for stroke patients' physical exercise, such as portable transcutaneous electrical stimulation (TENS), mirror therapy, home exercise program, and virtual reality exercise. Several studies have shown that telerehabilitation is not inferior than in-clinic physical exercise, and both showed significant improvement in post-stroke patients' motor function.Conclusions: Telerehabilitation can be the solution for post-stroke patient’s physical rehabilitation in the COVID-19 pandemic. This novel health innovation allowed the post-stroke patient to exercise at home and prevent them from the risk of COVID-19 infection.